The genesis and the challenges - Roberta Cohen; Francis M Deng (Forced Migration Review, 2008)
The need for international standards to protect andassist internally displaced persons arose directlyfrom the explosion of civil wars in the last decade ofthe 20th century that left tens of millions uprootedwithin the borders of their own countries.